The Location of the Fullest Manuscript of the Louth Park Abbey Chronicle, Brutus to 1413. (17th March 2020) - Smith, Trevor Russell
Abstract: This note discusses the Louth Park Abbey Chronicle, which survives in three manuscripts in varying levels of completeness, the fullest of which has changed hands several times since the only edition of the text was produced in 1891. Further study of the text and its two additional manuscripts has been impossible, however, as the fullest manuscript has been untraced since 1987, at the latest. This article examines the provenance of this lost manuscript and identifies its current location.